The multi-objective decision making methods based on MULTIMOORA and MOOSRA for the laptop selection problem - Esra Aytaç Adalı; Ayşegül Tuş Işık (Journal of Industrial Engineering International, 2017)
A decision making process requires the values of conflicting objectives for alternatives and the selection of the best alternative according to the needs of decision makers. Multi-objective optimization methods may provide solution for this selection. In this paper it is aimed to present the laptop selection problem based on MOORA plus full multiplicative form (MULTIMOORA) and multiobjective optimization on the basis of simple ratio analysis (MOOSRA) which are relatively new multi-objective optimization methods. The novelty of this paper is solving this problem with the MULTIMOORA and MOOSRA methods for the first time.
Keywords: 650; Multi-objective decision making; MULTIMOORA method; MOOSRA method; Laptop selection